STIL Overexpression Is Associated with Chromosomal Numerical Abnormalities in Non-Small-Cell Lung Carcinoma Through Centrosome Amplification - Shunsuke Ohtsuka; Hisami Kato; Rei Ishikawa; Hirofumi Watanabe; Ryosuke Miyazaki; Shin-ya Katsuragi; Katsuhiro Yoshimura; Hidetaka Yamada; Yasuhiro Sakai; Yusuke Inoue; Yusuke Takanashi; Keigo Sekihara; et al. (Current Oncology)
STIL is a regulatory protein essential for centriole biogenesis, and its dysregulation has been implicated in various diseases, including malignancies. However, its role in non-small-cell lung carcinoma (NSCLC) remains unclear. In this study, we examined STIL expression and its potential association with chromosomal numerical abnormalities (CNAs) in NSCLC using The Cancer Genome Atlas (TCGA) dataset, immunohistochemical analysis, and in vitro experiments with NSCLC cell lines designed to overexpress STIL. TCGA data revealed upregulated STIL mRNA expression in lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC), the two major subtypes of NSCLC. Immunohistochemical analysis of cases from our hospital (LUAD, n = 268; LUSC, n = 98) revealed STIL protein overexpression. To elucidate the functional role of STIL, an inducible STIL-overexpressing H1299 NSCLC cell line was generated. Overexpression of STIL in these cells promoted centrosome amplification, leading to chromosomal instability. Finally, analysis of arm-level chromosomal copy number alterations from the TCGA dataset revealed that elevated STIL mRNA expression was associated with CNAs in both LUAD and LUSC. These findings suggest that STIL overexpression is associated with CNAs in NSCLC, likely through centrosome amplification, which is linked to chromosomal instability and might represent a potential therapeutic target for NSCLC treatment.